Youth labour brigades in Yugoslavia and representations of volunteerism - Mithans, Gašper (Annales. Series historia et sociologia, 2022)
The author discusses the issue of volunteerism in labour actions in Yugoslavia raised by several scholars, distinguishing between different phases, which mostly corresponded to changes in the socialist regime and society in general. With its research based on literature and archival sources, the question of the voluntary character of the youth labour actions is explored. The district of Koper in the late 1950s and early 1960s, the crucial period in the process of the transformation of youth labour actions, is paid particular attention, drawing on the experiences of the brigadiers and the challenges that the People’s Youth had to face.
Keywords: azione di lavoro giovanile; Capodistria; Jugoslavia socialista; Jugoslavija; Koper; Ljudska mladina; mladina; mladinske delovne akcije; organizzazione giovanile; People’s Youth; prostovoljstvo; socialist Yugoslavia; volontariato; volunteerism; youth labour actions